The effect of Scarification and treatment with moving water on the germination of Sidr seeds and plant growth (Damascus University Journal of agriculture sciences, 2024)
This study was conducted in the Al-Haffah region on a private farm in Lattakia Governorate during the years 2020-2021 on the seeds of Zizyphu Spina trees, with the aim of studying the effect of moving, oxygenated, and non-moving water for a period of 2-4 days on the germination of seeds with 40 days scarification and without scarification.The results of the analysis of variance showed a significant difference between the treatments, where the treatment of oxygenated water for 24 hours was superior in the percentage of germination, which reached to 85%, compared to the untreated. The treatment with moving water during 2 days also achieved a better quality of seedlings represented by the length of the roots of the plant (16.1 cm) and its dry weight (10.9 g), and the average number of leaves (29 leaves), in addition to the length of the stem of the plant (34.3 cm).
Keywords: Zizyphu Spina seeds; moving water; Scarification; oxygenation; germination